Design and Build an Academic E-Reminder Application Using Mobile-Based Push Notification Technology - Lora Elyza (Jurnal Komputer, Informasi dan Teknologi, 2023)
One of the activities carried out in tertiary institutions is academic activity. Academic activities are arranged in an academic calendar that is used to schedule academic activities both in the short and long term. Information on the academic calendar is usually announced on bulletin boards, social media and even distributed through online student groups. Even though academic activities are routines that are often carried out by students, with so many academic activities, it is not uncommon for some important things to be forgotten. To overcome the problems above, we need an application that can help remind these students wherever and whenever they are. One way is to take advantage of the sophistication of an Android smartphone that is equipped with a push notification feature. The results of the study show that the application can run well on an Android smartphone and notifications appear automatically according to the data entered by the application user.